What about Provincial Institutions in Higher Education Policy in India? - Srivastava, Anamika; Koshal, Nandita (International Higher Education, 2018)
In this article, we take stock of provincial higher education institutions in India, which—advertently or not—have not yet caught the attention of policy makers. However, these institutions employ the majority of the teachers and cater to the needs of the majority of students in the country.